Smart lighting system / Muhammad Haris Khushairi Mohmad Kadir & Muhammad Nizamul Hakim Norzaki - Mohmad Kadir, Muhammad Haris Khushair; Norzaki, Muhammad Nizamul Hakim (2015)
The main purpose of this report is to state clearly about smart lighting system that using a component named Arduino Uno. This component has already been used widely in this platform. This project is made to fulfil our main objectives which is to investigate on how every component works in a complete circuit, to analyses the circuit design and also to understand its function , finally to carry out a simulation and determine a faults if any. The main component of this project is the sensor. A motion sensor and a passive infrared sensor, and also a micro controller which will be discussed thoroughly in the next chapter of this report. Thus, this project is very helpful as they are equipped with technology equipped devices yet it is still easy to handle and effective for a smart house.